A carbon-based material with a hierarchical structure and intrinsic heteroatom sites for sodium-ion storage with ultrahigh rate and capacity. Issue 37 (16th September 2021) - Cui, Xue-Yang; Lin, Xiao-Dong; Wang, Ya-Jing; Xu, Pan; Fan, Xiao-Xiang; Zheng, Ming-Sen; Chen, Jia-Jia; Dong, Quan-Feng
Abstract : A hierarchically structured and intrinsically-heteroatom-containing carbon-based material is constructed and employed as both cathode and anode for sodium-ion capacitors, achieving both high energy density and power density. Abstract : The storage of sodium ions with carbon materials has huge potential for large-scale application due to its resource-rich and environmental advantages. However, how to realize high power density, high energy density and long cycle life are the bottlenecks restricting its development. Herein, by using a facile synthesis strategy, a carbon-based framework with a hierarchical structure and intrinsic heteroatom sites which are the characteristics contributing to ultrahigh rate and capacity has been achieved. As a result, the hierarchical carbon-based material exhibits excellent performance when used as both the anode and cathode for sodium-ion capacitors (SICs), which can deliver a high energy density of 224 W h kg −1 (at 180 W kg −1 ), an ultrahigh power density of 17 160 W kg −1 (at 128 W h kg −1 ) and ultralong cycle life (91% capacity retention after 10 000 cycles at 2 A g −1 ), outperforming most of the previously reported SICs with other configurations.